The Golden Cockerel, 1914 and 1917, Designed by N. Goncharova. Specificity and Differences of Stage Design - Voytova Ramilya D. (Художественная культура, 2023)
This article is devoted to the study of the evolution of N. Goncharova’s artistic manner on the example of her stage designs for the 1914 and 1937 productions of The Golden Cockerel. The opera-ballet version of The Golden Cockerel is often described in detail in works devoted to S. Diaghilev and his theatre company, and the creative work of N. Goncharovа and M. Larionov. However, due to the fact that Goncharovа’s graphic heritage of the 1930s-1950s has been little studied so far, the scene design of the 1937 ballet version is almost not considered, nor is it traced within the general evolution of N. Goncharovа’s style. Comparing the two versions of scene design, 23 years apart, as well as identifying the influence of the changed external factors and the social context makes it possible to visually examine the changes in N. Goncharova’s artistic manner during emigration.